Avaliação hidrológica e relação entre disponibilidade e demanda hídrica na Bacia hidrográfica do Rio Sorocaba - Abreu, Marcio Costa (Universidade Federal de São Carlos, 2015)
This study aimed to contribute to the understanding of the dynamics of water resources in the watershed of Sorocaba river and establish relationships between availability and water demand. Initially it was proposed a quantitative model of how to distribute the water in the different stages of the water cycle, from the moment of the rains, to flow to your river mouth, considering the intermediate steps between these two events, including human interventions represented by withdrawals of water from springs. For it was carried out the survey and analysis of hydrological data available and estimated those without measurements through the water balance. Set up for the series evaluated the climatological normal temperatures and rainfall and the average flow rate in river mouth, ie the watercourse that is base level of the watershed. The following parameters were estimated: potential and real evapotranspiration, surplus and water deficit. The average rainfall in the basin for the period 2006-2012 was 1,337 mm.year-1 , the average annual temperature 21.2°C, the ETP and ETR 1,011 mm.year-1 and 999 mm.year-1 , respectively, the water surplus 338 mm.year-1 , the average flow in river mouth 360 mm.year-1 and the flow derived and actually consumed by the users of 16 mm.year-1 . The water availability was adopted as the flow with 95% permanence (Q95%), estimated at 24.1 m3 .s-1 and the demands were obtained based on data from granting processes and by other methodologies, enabling a comparison between the results. Demands for major consumptive uses identified in the watershed were calculated with the following results: human supply 6.20 m 3 .s-1 ; industrial 1.83 m 3 .s-1 ; irrigation 3.59 m 3 .s-1 ; and animal consumption 0.24 m 3 .s-1 . The relationship between availability versus demand was considered and the results allowed indicate that the current situation of water resources across its use is very critical.
Hydrologic evaluation and relationship between water availability and demand in the Sorocaba river watershed - SP
Keywords: Recursos hídricos - desenvolvimento; Balanço hidrológico; Water resources development; Water balance (Hidrology); Water resources management; water escassez; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS